2011
DOI: 10.1007/978-3-642-22922-0_15
|View full text |Cite
|
Sign up to set email alerts
|

Towards Reducing Taxicab Cruising Time Using Spatio-Temporal Profitability Maps

Abstract: Abstract. Taxicab service plays a vital role in public transportation by offering passengers quick personalized destination service in a semiprivate and secure manner. Taxicabs cruise the road network looking for a fare at designated taxi stands or alongside the streets. However, this service is often inefficient due to a low ratio of live miles (miles with a fare) to cruising miles (miles without a fare). The unpredictable nature of passengers and destinations make efficient systematic routing a challenge. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 9 publications
0
66
0
Order By: Relevance
“…For frequentist method, we also need to generate replicas in order to do the Monte Carlo simulation. For this purpose, for each given synthetic data set, we first apply EM algorithm to learn the overall rate of spatial features: q Real data experiment set-up For real data experiments, we use the taxi data in Shanghai, China( [12]). The data is collected with a frequency of 300 seconds from 12am, May 29, 2009 to 6pm, May 30,2009.…”
Section: Experiments Set-upmentioning
confidence: 99%
“…For frequentist method, we also need to generate replicas in order to do the Monte Carlo simulation. For this purpose, for each given synthetic data set, we first apply EM algorithm to learn the overall rate of spatial features: q Real data experiment set-up For real data experiments, we use the taxi data in Shanghai, China( [12]). The data is collected with a frequency of 300 seconds from 12am, May 29, 2009 to 6pm, May 30,2009.…”
Section: Experiments Set-upmentioning
confidence: 99%
“…The idea is to identify, offline, the routes and destinations that historically produce more fares for taxis. In [9], the authors use historical data as experience and derive a Spatio-Temporal Profitability (STP) map to guide cruising taxicabs looking for customers. This method avoids systematic routing, which is impractical in most cases.…”
Section: Related Workmentioning
confidence: 99%
“…Ebendt et al [11] suggested reducing the fleet travel times by measuring real-time travel using FCD in Berlin. Powell et al [12] generated spatiotemporal profitability maps to help taxi drivers reduce cruising time.…”
Section: Introductionmentioning
confidence: 99%